2010
DOI: 10.1155/2010/676243
|View full text |Cite
|
Sign up to set email alerts
|

Hexavalent Chromium Removal by a Paecilomycessp. Fungal Strain Isolated from Environment

Abstract: A resistant and capable fungal strain in removing hexavalent chromium was isolated from an environment near of Chemical Science Faculty, located in the city of San Luis Potosí, Mexico. The strain was identified as Paecilomyces sp., by macro- and microscopic characteristics. Strain resistance of the strain to high Cr (VI) concentrations and its ability to reduce chromium were studied. When it was incubated in minimal medium with glucose, another inexpensive commercial carbon source like unrefined and brown suga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(22 citation statements)
references
References 33 publications
1
21
0
Order By: Relevance
“…Moreover, Paecilomyces sp. showed its capacity to reduce 50 mg/l Cr (VI), with the associated production of Cr (III) in the growth medium after 7 days of incubation [68]. Congeevaram et al [69], reported that Aspergillus sp.…”
Section: Fungal Chromium Resistancementioning
confidence: 99%
“…Moreover, Paecilomyces sp. showed its capacity to reduce 50 mg/l Cr (VI), with the associated production of Cr (III) in the growth medium after 7 days of incubation [68]. Congeevaram et al [69], reported that Aspergillus sp.…”
Section: Fungal Chromium Resistancementioning
confidence: 99%
“…The final set of flasks were used for subsequent plating and isolation of fungi on sludge containing MSM plates. The pH of the medium was maintained at 5.30 with 100 mM L -1 citrate-phosphate buffer 20 . The inoculated petriplates were incubated at 28 ºC for seven days.…”
Section: Isolation and Identification Of Potential Fungal Strainmentioning
confidence: 99%
“…However, its requirement for plants is debatable 4,5 . The divalent oxyanions of Cr(VI) are 100-1000 times more toxic, more soluble in water, and more motile and strong oxidizing agent than Cr(III) 6,7 ; hence it has been declared lethal for all living organisms 8 . Thus it is imperative to consider the significance of Cr for soil biota as one gram of soil may comprise 0.005-3 mg of Cr 9 .…”
Section: Introductionmentioning
confidence: 99%